FTIR Analysis of ZnO-Functionalized Activated Carbon Derived from Oil Palm Empty Fruit Bunches for Potential Photocatalytic Applications - Lestari, Devi; Masriah, Imas; Hasibuan, Adelia Yesya Putri; Pratiwi, Pina Budiarti (Jurnal Bio-Geo Material Dan Energi, 2026)
This study investigates the surface chemical characteristics of ZnO-functionalized activated carbon (AC) derived from oil palm empty fruit bunches (OPEFB) using Fourier Transform Infrared (FTIR) spectroscopy. Activated carbon was prepared through carbonization at 400 °C followed by chemical activation using KOH. ZnO functionalization was performed via the sol–gel method with a nominal ZnO loading of 10 wt% relative to AC. FTIR analysis revealed dominant absorption bands corresponding to O–H stretching (~3430 cm⁻¹), C=O stretching (~1630 cm⁻¹), and C–O vibrations (~1050–1100 cm⁻¹), indicating the presence of oxygen-containing surface functional groups. The appearance of a characteristic Zn–O vibrational band in the 450–600 cm⁻¹ region confirmed the incorporation of ZnO within the composite structure. Minor peak shifts and variations in band intensity observed after ZnO modification suggest changes in the local chemical environment and possible interactions between ZnO nanoparticles and oxygen-containing functional groups. However, FTIR analysis alone does not provide definitive confirmation of specific interfacial bonding configurations. The results indicate that KOH activation preserved reactive oxygenated functionalities that remained stable after ZnO incorporation. The coexistence of porous AC characteristics and ZnO-associated vibrational features suggests that the synthesized AC/ZnO composite possesses surface chemical properties relevant for adsorption-assisted photocatalytic applications. This work demonstrates the potential valorization of OPEFB biomass into functional carbon-based hybrid materials.